Le Journal pour Mlle de Menou : exemple de l’art de vivre en réclusion - Kulesza, Monika (L’art de vivre, de survivre, de revivre. Approches littéraires. Le 50e anniversaire des études romanes à l’Université de Łódź, 2022)
This article presents a hybrid work by Mme de Murat, Le Journal pour Mlle deMenou, written between 1708 and 1709 in the château de Loches where the countess wasexiled. Mme de Murat copes with the oppression of royal power by leading a life similarto that from which she was cut off. She finds consolation in the writing of the diary andaffection for her cousin, she writes poems and organises literary and social life in exiledemonstrating freedom of her spirit.